Hinter den Kulissen des Ostmarken Vereins. Zur Entstehung der ,Ostmarkenromane' - Wojtczak, Maria (Studia Germanica Posnaniensia, 2018)
The cultural life of Gennans living in the Grand Duchy of Poznan established in 1815 was animated by two important institutions: the Imperial Library (Kaiser Wilhelm Bibliothek), founded in 1902, and the German Union of the Eastern Borderland (Ostmarkenverein), established in 1894. On the initiative of these two institutions a list of ,,recommended Poznan literature“ was compiled. The list included over forty novels, stories and plays by German writers, all conforming to the idea of the so-called „German mission in the East“. Similar lists that fallowed were seemingly a result of the 1913 literary contest for the best novel about the Province of Poznan. The Ostmarkenliteratur writers are unknown, difficult to identify. They were propably commissioned by Ostmarkenverein to write their novels an aim to support the contemporary Prussian policy towards Poland.